Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.triboint.2017.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Looking into a laser textured piston ring-liner contact

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 52 publications
(98 reference statements)
1
50
0
Order By: Relevance
“…This is particularly significant for contacts with parallel and flat surfaces, such as those encountered in mechanical seals and parallel thrust bearings. Furthermore, the subambient pressure zones formed in textures close to the contact inlet due to the fluid cavitation phenomenon responsible for the aforementioned micro-hydrodynamic bearing effect may also contribute to drawing additional lubricant into the contact (inlet-suction effect) [27,29,30]. However, it needs to be pointed out that an inappropriate choice of texture parameters (i.e., texture depth, width, and density) may lead to detrimental effects due to the excessive increase of the cavitation zones, which may reduce the local film thickness and the load carrying capacity [31].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly significant for contacts with parallel and flat surfaces, such as those encountered in mechanical seals and parallel thrust bearings. Furthermore, the subambient pressure zones formed in textures close to the contact inlet due to the fluid cavitation phenomenon responsible for the aforementioned micro-hydrodynamic bearing effect may also contribute to drawing additional lubricant into the contact (inlet-suction effect) [27,29,30]. However, it needs to be pointed out that an inappropriate choice of texture parameters (i.e., texture depth, width, and density) may lead to detrimental effects due to the excessive increase of the cavitation zones, which may reduce the local film thickness and the load carrying capacity [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth highlighting that the Reynolds equation based model used in this work is not suitable to properly reproduce the lubricant flow within pores or other very deep topographic features (see more in-depth discussions about the effect of dimples on lubrication in Refs. [19,20]).…”
Section: Resultsmentioning
confidence: 99%
“…The change of direction makes the cavitated region of the outlet the new inlet region in the subsequent stroke. 46,47 It was also observed that the region of starvation can occur for 5% of the stroke. However, this will be dependent upon the viscosity of the lubricant.…”
Section: Methodsmentioning
confidence: 96%